2008
DOI: 10.1083/jcb.200805048
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII locally encodes L-type channel activity to signal to nuclear CREB in excitation–transcription coupling

Abstract: Communication between cell surface proteins and the nucleus is integral to many cellular adaptations. In the case of ion channels in excitable cells, the dynamics of signaling to the nucleus are particularly important because the natural stimulus, surface membrane depolarization, is rapidly pulsatile. To better understand excitation–transcription coupling we characterized the dependence of cAMP response element–binding protein phosphorylation, a critical step in neuronal plasticity, on the level and duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
178
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(196 citation statements)
references
References 108 publications
(147 reference statements)
11
178
0
7
Order By: Relevance
“…Furthermore, co-induction of VGLUT2 and Narp after prolonged hyperactivity is not sensitive to inhibition by TrkB-Fc nor is it blocked by inhibition of tyrosine receptor kinase activity with K-252a. Together, our data support the model of E-T coupling that can utilize discrete temporal and spatial requirements for Ca 2ϩ signal transcription to support enhanced gene transcription (41,42,44,45).…”
Section: E-t Coupling Via Casupporting
confidence: 74%
See 2 more Smart Citations
“…Furthermore, co-induction of VGLUT2 and Narp after prolonged hyperactivity is not sensitive to inhibition by TrkB-Fc nor is it blocked by inhibition of tyrosine receptor kinase activity with K-252a. Together, our data support the model of E-T coupling that can utilize discrete temporal and spatial requirements for Ca 2ϩ signal transcription to support enhanced gene transcription (41,42,44,45).…”
Section: E-t Coupling Via Casupporting
confidence: 74%
“…Here, we describe an activity-dependent mechanism of VGLUT2 and Narp gene induction in mature neocortical neurons that involves excitation-transcription (E-T) coupling, a process initiated by Ca 2ϩ signal transcription that results in early, intermediate-early, and long term changes in gene expression (41)(42)(43)(44)(45). E-T coupling in central cortical neurons can be initiated by Ca 2ϩ influx through L-type voltage-gated Ca 2ϩ channels (VGCCs) and includes calmodulin-signaling and phosphorylation via Ca 2ϩ / calmodulin-dependent protein kinases (CaMK) and mitogen-activated protein kinases (MAPKs) (45)(46)(47)(48).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on cell type, developmental stage and subcellular location, different Ca V subtypes are involved in orchestrating Ca 2+ -dependent signaling; Ca V 1 and Ca V 2 channels trigger transcription-dependent forms of synaptic plasticity (Ca V 1.2 and Ca V 1.3) (Wheeler et al, 2008) and fast neurotransmitter release (Ca V 2.1-3) (Dunlap et al, 1995;Catterall and Few, 2008;Pan and Zucker, 2009), whereas, Ca V 3 and Ca V 1.3 channels, that activate closer to the resting membrane potential, are involved in regulating cell excitability and shaping neuronal firing patterns Perez-Reyes, 2003;McKay et al, 2006;Xu and Lipscombe, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, experimental approaches based on RNA interference have been used in tumour pituitary cells to examine signal molecules/receptors involved in SRIF functions (Theodoropoulou et al 2006;Ben-Shlomo et al 2007). In different experimental models (Nie et al 2007;Hao et al 2008;Wheeler et al 2008), including neuroendocrine cells (Basavappa et al 1999) transients which have been demonstrated as an effective manner to maintain GH exocytosis (Cervia et al 2002b;Dominguez et al 2007). In neurons, exocytosis seems to depend on multiple factors, including the activation of CaMKII signalling (which causes an increase of [Ca 2+ ] i ) and proceeds via delayed fusion pore opening (Kolarow et al 2007).…”
Section: Discussionmentioning
confidence: 99%